Strategi Inovasi Perusahaan Keluarga Sekala UKM Studi Kasus Industri Batik Daerah Istimewa Yogyakarta - Antori, Antori (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research is conducted by qualitative approach of case study method, the main purpose is to explore the strategic actions of small-scale family enterprises in batik industry based on innovation strategy (SI). The data was collected through in-depth interviews of ten SME batik industry players in Yogyakarta. The findings show that the pattern of SI contractor business actors tends to innovate products and distribution innovations that serve as an alternative solution to overcome the problems encountered. In addition, found the slow growth of SMEs scale batik companies have been due to in addition to prioritizing external problems, but also the lack of correlation between solutions taken with the problems encountered.